1995
DOI: 10.1104/pp.109.4.1441
|View full text |Cite
|
Sign up to set email alerts
|

Subsaturating Ribulose-1,5-Bisphosphate Concentration Promotes Inactivation of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase (Rubisco) (Studies Using Continuous Substrate Addition in the Presence and Absence of Rubisco Activase)

Abstract: , lllinois 61801 (A.R.P.)We developed a continuous-addition method for maintaining subsaturating concentrations of ribulose-1,5-bisphosphate (RuBP) for severa1 minutes, while simultaneously monitoring its consumption by ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco). This method enabled us to observe the effects of subsaturating RuBP and CO, concentrations on the activity of Rubisco during much longer periods than previously studied. At saturating CO,, the activity of the,enzyme declined faster w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Ribulose-1,5-bisphosphate is a potent inhibitor of decarbamylated Rubisco (Chu and Bassham 1975;Jordan and Chollet 1983), and this inhibition is ameliorated by Rubisco activase (Portis et al 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Ribulose-1,5-bisphosphate is a potent inhibitor of decarbamylated Rubisco (Chu and Bassham 1975;Jordan and Chollet 1983), and this inhibition is ameliorated by Rubisco activase (Portis et al 1995).…”
Section: Discussionmentioning
confidence: 98%
“…The potential mechanism(s) responsible for Rubisco fallover are thought to be the loss of catalytically competent sites due to either the tight binding of inhibitory isomers of ribulose-P 2 and/or decarbamylation (Edmondson et al 1990c;Portis et al 1995;Zhu et al 1998). The inhibitors appear to be generated by isomerization and rearrangement of ribulose-P 2 in the active site during Rubisco catalysis (Paech et al 1978;Chen and Hartman 1995;Pearce and Andrews 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Rubisco fallover under various conditions was initially characterized in several pioneering reports (Edmondson et al 1990a;Zhu and Jensen 1991b;Portis et al 1995). In these studies, low levels of ribulose-P 2 , CO 2 , and pH were reported to increase the extent and/or rate of fallover.…”
Section: Introductionmentioning
confidence: 98%
“…Activase Specificity Assay-The ability of RuBP-inhibited Rubisco to be activated by Rubisco activase was assessed by a spectrophotometric assay at 25°C that couples the product of RuBP carboxylation, 3-phosphoglycerate, to the oxidation of NADH (10,39). Reaction mixtures contained 50 mM Tricine, pH 8.0, 12 mM MgCl 2 , 10 mM NaHCO 3 , 10 mM dithiothreitol, 2 mM ATP, 2 mM RuBP, 10 mM phosphocreatine, 750 M NADH, and coupling enzymes (60 IU/ml 3-phosphoglycerate kinase, 300 IU/ml triose-phosphate isomerase, and 30 IU/ml each of creatine phosphokinase, glyceraldehyde-3-phosphate dehydrogenase, glycerol-3-phosphate dehydrogenase, and carbonic anhydrase).…”
Section: Strains Andmentioning
confidence: 99%
“…Activase couples the energy of ATP hydrolysis to the release of inhibitory sugar phosphates bound to both carbamylated and decarbamylated Rubisco active sites. High activase activity, along with high concentrations of RuBP, allows rapid and complete carbamylation to occur via a quasi-equilibrium state (10,11) and reverses inhibition by misprotonated sugar phosphates (12). Activase is essential for photosynthesis in higher plants.…”
mentioning
confidence: 99%